2019
DOI: 10.3389/fgene.2019.00871
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of CYP3A4*22 on Tacrolimus Pharmacokinetics and Outcome in Clinical Practice at a Single Kidney Transplant Center

Abstract: Background: Although there is evidence that the CYP3A4*22 variant should be considered in tacrolimus dosing in renal transplantation, its impact beyond tacrolimus dose requirements remains controversial.Methods: In a cohort of 121 kidney transplant recipients, we analyzed the CYP3A4*1B, CYP3A4*22, and CYP3A5*3 alleles and the ABCB1 variants 1236C>T, 2677G>T/A, and 3435C>T for their impact on exposure and dose requirement. Relevant clinical outcome measures such as acute rejection within the first year after tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 38 publications
0
14
1
Order By: Relevance
“…In addition, CYP3A4 is the most abundant cytochrome P450 enzyme in human hepatocytes and is also responsible for tacrolimus metabolism. Two intragenic CYP3A4 SNPs have been hypothesized to contribute to tacrolimus interindividual PK variability [27,28]. In addition to SNPs in genes that encode proteins that influence tacrolimus metabolism, germline variants in drug transporters may also contribute to tacrolimus PK variability.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, CYP3A4 is the most abundant cytochrome P450 enzyme in human hepatocytes and is also responsible for tacrolimus metabolism. Two intragenic CYP3A4 SNPs have been hypothesized to contribute to tacrolimus interindividual PK variability [27,28]. In addition to SNPs in genes that encode proteins that influence tacrolimus metabolism, germline variants in drug transporters may also contribute to tacrolimus PK variability.…”
Section: Introductionmentioning
confidence: 99%
“…Besides the assessment of dose‐requirement, genotyping for CYP3A5 was reported to facilitate rapid dose‐finding and improved achievement of target tacrolimus concentration in kidney transplant patients 39,40 . For refining genotype‐based tacrolimus dosing, CYP3A4*22 resulting in reduced CYP3A4 expression has recently been suggested to be integrated with CYP3A5 genotype information 7,41,42 . Nonetheless, variability in tacrolimus dose‐requirement appears to be far from that is explainable by CYP3A5*1 and CYP3A4*22 (<20%) 43 .…”
Section: Discussionmentioning
confidence: 99%
“…To date, multiple studies have confirmed that in kidney transplant recipients, sub-therapeutic tacrolimus levels or high tacrolimus IPV can result in increased dnDSA formation [ 25 , 65 , 66 , 67 , 68 , 69 , 70 , 71 ]. In the modern era, there has been increasing interest in the identification and validation of genetic variations that contribute to IPV [ 72 , 73 ]. Germline mutations in ATP-binding cassette B1 gene (ABCB1) and CYP3A4/5 probably contribute to interindividual tacrolimus PK variability [ 3 , 17 , 74 ].…”
Section: Intra-individual and Inter-individual Tacrolimus Pk Variamentioning
confidence: 99%
“…Single nucleotide polymorphisms (SNPs) in CYP3A5 could contribute 40%–50% of inter-individual PK variability [ 75 , 76 ]. Two intragenic CYP3A4 SNPs are hypothesized to cause inter-individual PK variability [ 72 , 73 ]. Genetic variants in drug transporters may also add to tacrolimus’ PK variability.…”
Section: Intra-individual and Inter-individual Tacrolimus Pk Variamentioning
confidence: 99%